The Influence Of English Language Proficiency On Pharmacists’ Communication Skills In Pharmaceutical Services (Systematic Review) - Ahmad Nurwanto; Dwi Wulan Apriani (CV. ITTC INDONESIA, 2025)
This systematic review aims to analyze the influence of English language proficiency on pharmacists' communication skills in pharmaceutical services. The review of five studies indicates that strong English proficiency significantly enhances the effectiveness of medication counseling, interdisciplinary collaboration, and comprehension of scientific literature supporting evidence-based practice. The findings highlight the importance of contextual and continuous English language training for pharmacists, as well as the integration of English for Pharmacy Purposes (EPP) into pharmacy education curricula. It can be concluded that English proficiency is an essential competency that supports the quality of pharmaceutical care and patient safety.